The Growth Effect Of Capital Inflows: Evidence From Nigeria Using ARDL Approach - Akinwale, S. O.; Adekunle, O. E. (Archives of Business Research, 2019)
Developing countries like Nigeria lacked sufficient domestic capital formation to stimulate growth which juxtaposed the need for foreign capital. This study investigated the growth implication of foreign capital inflows in Nigeria. The study adopted Augmented Dickey – Fuller (ADF), Bound Test and Autoregressive Distributed Lag to evaluate the relationship between real gross domestic product, foreign direct investment, foreign portfolio investment, external debt and savings. The results of the unit root test indicated that foreign direct investment and foreign portfolio investment are stationary at level while real gross domestic, external debt and savings are not stationary at first differences. The result of the bound test indicated that there is long run equilibrium relationship between different order foreign direct investment, foreign portfolio investment, external debt and savings and real gross domestic product. Findings from the study showed that foreign direct investment and foreign portfolio influenced economic growth in short run but not in the long run. Also, external debt was found to have negative effect on economic growth both in the short run and long run. Based on the causality test, it was found that foreign direct investment, foreign portfolio investment and external debt did not cause real gross domestic product while causality flowed from savings to real gross domestic product and vice versa. The study thus concluded that, the inflow of foreign capital had mixed effect on economic growth both in the short run and long run. The study recommended that government should formulate policies that will stimulate the inflow of foreign direct investment in the economy, government should introduce more liquid and advanced instruments in the capital market in order to attract foreign portfolio investment and finally foreign borrowings should be mainly used for developmental purpose through the provision of infrastructural facilities in order to promote the growth of domestic investment and foreign direct investment.